Using Challenge Educational Technology to Increase Students' Vocabulary - Muqaddas Egamberdieva; Kamilova Okhista (Researchparks Publishing, 2022)
In this article, the importance of using modern methods in teaching of English language and literature at schools and the issue of creating a problematic situation based on contrasting and comparing language phenomena with the use of problematic educational technologies in teaching English today are widely covered.